The clinical impact of Prostate Imaging–Reporting and Data System classification in patients with haemospermia undergoing multiparametric magnetic resonance imaging of the prostate. (10th March 2021) - Kilic, Mert; Coskun, Bilgen; Vural, Metin; Musaoglu, Ahmet; Esen, Tarik; Balbay, Mevlana Derya
Abstract: In this study, we evaluated the role of the Prostate Imaging–Reporting and Data System (PI‐RADS) classification of multiparametric magnetic resonance imaging (mpMRI) to determine the likelihood of prostate cancer (PCa) in patients with haemospermia. Fifty‐one patients presenting with haemospermia between 2018 and 2020 were included in this retrospective study. Forty‐two of the patients (82.4%) were over 40 years, and the median prostate‐specific antigen (PSA) level was 1.4 ng/ml. Fourteen of the patients (27.5%) had recurrent haemospermia. All patients underwent mpMRI, and assessments were classified according to PI‐RADS v2. The mpMRI revealed PI‐RADS one to four lesions in 10 (19.6%), 30 (58.8%), 6 (11.8%) and 5 (9.8%) patients respectively. One patient with PI‐RADS 3 and five with PI‐RADS 4 lesions underwent cognitive fusion prostate biopsy depending on MRI findings, and two patients with PI‐RADS 4 lesions were diagnosed with PCa. Patients with haemospermia and risk factors, that is aged over 40 years, a high PSA level or familial history of PCa, need a more thorough evaluation with mpMRI.